Structural Relationship Between Pay Administration and Employee’s Commitment: A Case Study in Pos Malaysia Berhad - Abd Razak, Mohd Ridwan; Ali, Enah (International Business Education Journal, 2021)
Pay administration is one of the most important functions in the organisational administration domain. Contemporary research shows that the capability of an organisation’s administrator to share the information about pay administration, encourage employees’ engagement in pay administration, and enforce good performance evaluation may have a positive and significant influence on employees’ commitment toward the organisation. However, there is a limited explanation about the importance of pay administration as an important factor in the organisational pay administration domain. This study is performed to analyse the importance and performance of each element in pay administration towards employee commitment. Main data are collected from 400 self-report questionnaires filled by the employees of Pos Malaysia Berhad in Klang Valley. The results of Partial Least Square - Structural Equation Modeling (PLS-SEM) stipulate that pay administration is positively and significantly interrelated with employees’ commitment. Therefore, the results show that the ability of an organisation’s pay administrator to successfully implement effective information sharing, encourage employee engagement, and practice good performance evaluation in administering pay systems may enhance employees’ commitment to the organisation.